2017
DOI: 10.1111/aji.12636
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection status and infertility causes in couples seeking fertility treatment—Indicator of impaired immune response?

Abstract: Our results suggest HBV infection in either partner was associated with tubal infertility. HBV infection in either partner probably increases the risk of pelvic infection in female partner through impaired immune response to sexually transmitted infections, with consequent tubal damage and infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
1
19
0
2
Order By: Relevance
“…Earlier studies in SARS-CoV, which also targeted the same receptor, have revealed that numerous patients had evidence of testicular inflammation (orchitis) [ 230 ]. Indeed, a range of other viral infections such as HIV, mumps, hepatitis B, and human papillomavirus has been shown to cause male sterility, altered expression of hormones, and may even be linked to increased risk of testicular cancer [ 231 , 232 , 233 , 234 , 235 ]. One study demonstrated that the ratio of testosterone and follicle-stimulating hormone to serum luteinizing hormone was significantly decreased in young adult male COVID-19 patients ( n = 81) compared to controls ( n = 100) [ 229 ].…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
“…Earlier studies in SARS-CoV, which also targeted the same receptor, have revealed that numerous patients had evidence of testicular inflammation (orchitis) [ 230 ]. Indeed, a range of other viral infections such as HIV, mumps, hepatitis B, and human papillomavirus has been shown to cause male sterility, altered expression of hormones, and may even be linked to increased risk of testicular cancer [ 231 , 232 , 233 , 234 , 235 ]. One study demonstrated that the ratio of testosterone and follicle-stimulating hormone to serum luteinizing hormone was significantly decreased in young adult male COVID-19 patients ( n = 81) compared to controls ( n = 100) [ 229 ].…”
Section: How Might Ergothioneine Be Beneficial In Alleviating Covimentioning
confidence: 99%
“…Более высокая, по сравнению с популяционной, частота встречаемости вирусных гепатитов С и В, обнаруженная нами в подгруппе бесплодных муж-чин, соответствует результатам аналогичных работ, выполненных в других странах [22], авторы которых отметили, что у больных гепатитом мужчин наблю-даются менее высокие показатели объема эякулята, концентрации и подвижности сперматозоидов.…”
Section: Discussionunclassified
“…Impaired immune response is supposedly one of the noteworthy linkage between the two. 86 Hepatitis can also affect the success of in vitro fertilization (IVF). 87,88 Glucagon-like peptide (GLP) regulates secretion of insulin and maintains the balance between the requirement of sugar in the body by causing excess to be converted into glycogen.…”
Section: Liver Diseasementioning
confidence: 99%